Genetic markers as a predictive tool based on statistics in medical practice: ethical considerations through the analysis of the use of HLA-B*27 in rheumatology in France - Colineaux, Hélène; Ruyssen-Witrand, Adeline; Cambon-Thomsen, Anne (Frontiers in Genetics, 2015)
INTRODUCTION. The use of genetic predictive markers in medical practice does not necessarily bear the same kind of medical and ethical consequences than that of genes directly involved in monogenic diseases. However, the French bioethics law framed in the same way the production and use of any genetic information. It seems therefore necessary to explore the practical and ethical context of the actual use of predictive markers in order to highlight their specific stakes. In this study, we document the uses of HLA-B*27, which are an interesting example of the multiple features of genetic predictive marker in general medical practice. MATERIAL & METHODS. The aims of this monocentric and qualitative study were to identify concrete and ethical issues of using the HLA-B*27 marker and the interests and limits of the legal framework as perceived by prescribers. In this regard, a thematic and descriptive analysis of five rheumatologists’ semi-structured and face-to-face interviews was performed. RESULTS. According to most of the interviewees, HLA-B*27 is an “overframed” test because they considered that this test is not really genetic or at least does not have the same nature as “classical genetic tests”; HLA-B*27 is not concerned by the ethical challenges of genetic test; the major ethics stake of this marker is not linked to its genetic nature but rather to the complexity of the probabilistic information. This study allows also showing that HLA-B*27, validated for a certain usage, may be used in different ways in practice. DISCUSSION. This marker and its clinical uses underline the challenges of translating both statistical concepts and unifying legal framework in clinical practice. This study allows identifying some new aspects and stakes of genetics in medicine and shows the need of additional studies about the use of predictive genetic markers, in order to provide a better basis for decisions and legal framework regarding these practices.